Challenges in the management of pregnancy complicated by maternal Diamond Blackfan Anaemia: a case report - Tabassum, Shumaila; Shah, Fatima Ashfaq; O'Hare, Rachael (Journal of the Pakistan Medical Association, 2022)
Diamond Blackfan Anaemia (DBA) is a rare genetic disorder, affecting red blood cells. Pregnancy in women affected by DBA should be managed as a high-risk pregnancy, as it may trigger the relapse of anaemia, and is associated with both maternal and foetal complications. Corticosteroids are the first line of treatment, but a low threshold for blood transfusion should be considered to correct low haemoglobin in pregnancy. An adequate multidisciplinary input and planning is the key to ensure optimal perinatal outcome. We decided to report this case to highlight the implications of pregnancy on DBA and vice versa, taking into consideration the safest approach for the best possible outcomes for the mother and her baby. Keywords: Diamond Blackfan Anaemia. Red blood cell disorder. Blood transfusion. Pregnancy outcome. Continuous...